Research on intelligent detection method of new energy vehicle power battery based on improved ViBe algorithm - Lei Gu (EAI Endorsed Transactions on Energy Web)
Background: Traditional foreground detection methods for new energy vehicles using the ViBe algorithm often suffer from ghosting effects, which can obscure the accurate detection of moving targets.